2006
DOI: 10.1111/j.1442-2042.2006.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival under maintenance gemcitabine chemotherapy for metastatic transitional cell carcinoma

Abstract: We report a case of a 74-year-old patient who received 41 courses of maintenance therapy with gemcitabine over a length of 28 months for metastatic transitional cell carcinoma. One year earlier the patient had received three cycles of adjuvant cisplatin-based combination chemotherapy after nephro-ureterectomy for a locally advanced urothelial cancer of the right renal pelvis. This case demonstrates a paradigm shift in the palliative treatment of advanced urothelial cancer, with the implementation of more toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In this regard, gemcitabine is the first-ever chemotherapeutic agent that has been demonstrated to be capable of long-term control of tumor growth in a preclinical animal model of high-grade meningioma. Since gemcitabine has been reported to have an excellent, low toxicity profile suitable for long-term administration [ 17 , 27 30 ], our results suggest gemcitabine may be highly promising and advantageous in the long-term management of high-grade meningioma. It needs to be emphasized here that the gemcitabine regimen used in our xenograft study (intraperitoneal gemcitabine 20 mg/kg, twice a week for 4 weeks, given at the time of tumor regrowth) was not optimized and was far less intense compared with those (intraperitoneal gemcitabine 100∼125 mg/kg, twice a week continuously) widely used to treat xenograft tumors in nude mice [ 31 , 32 ], apparently allowing for increased dosing in future experiments.…”
Section: Discussionmentioning
confidence: 79%
“…In this regard, gemcitabine is the first-ever chemotherapeutic agent that has been demonstrated to be capable of long-term control of tumor growth in a preclinical animal model of high-grade meningioma. Since gemcitabine has been reported to have an excellent, low toxicity profile suitable for long-term administration [ 17 , 27 30 ], our results suggest gemcitabine may be highly promising and advantageous in the long-term management of high-grade meningioma. It needs to be emphasized here that the gemcitabine regimen used in our xenograft study (intraperitoneal gemcitabine 20 mg/kg, twice a week for 4 weeks, given at the time of tumor regrowth) was not optimized and was far less intense compared with those (intraperitoneal gemcitabine 100∼125 mg/kg, twice a week continuously) widely used to treat xenograft tumors in nude mice [ 31 , 32 ], apparently allowing for increased dosing in future experiments.…”
Section: Discussionmentioning
confidence: 79%
“…Lehmanne et al . reported administering 41 cycles of GEM maintenance monotherapy over a 28‐month period . In the current study, a maximum of 49 doses were administered.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance treatment in our study, the median (range) of number of cycles was (1-12)cycles with median dose of cycle (1000-1800mg) while Muto et al (12) the median was (2-49 ) cycles with median dose of cycle (500-1795mg), Kus and Aktas (14) the Median 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) cycles with median dose of cycle (500-1800mg) and Lehmann et al (15) reported administrating 41 cycles of GEM maintenance monotherapy with cumulative total dose of gemcitabine 88.500mg.…”
Section: Discussionmentioning
confidence: 46%
“…In Lehmann et al (15) , case report of a 74-yearold man with widespread metastatic lung and retroperitoneal transitional cell carcinoma. Having been diagnosed with pT3 G2-3 urothelial cancer of the renal pelvis in 1999, the patient underwent a right nephroureterectomy and subsequently underwent adjuvant chemotherapy consisting of three cycles of cisplatin and methotrexate, followed by palliative maintenance gemcitabine monotherapy, with dosing of 1200 mg/m2 body surface on days 1 and 8 of a 21-day cycle.…”
Section: Discussionmentioning
confidence: 99%